Part XI – November 1968 - Papers - The Determination of Rapid Recrystallization Rates of Austenite at the Temperatures of Hot Deformation - G. A. Wilber; J. R. Bell; J. H. Bucher; W. J. Childs (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1969)
A technique for determining recrystallization times as short as 0.10 sec was developed utilizing the "Gleeble", a commercially available testing system designed for the study of short-time, high-temperaLure themal and mechanical processes. The procedure consisted of heating a small tensile specimen to a given temperature of hot deformation, loading to a given reduction in area, unloading, delaying various intervals at temperature, and then reloading- to failure. The magnitude of the ultimate load obtained upon reloading decreased with delay lime as recrys-lallization proceeded. The technique was applied to austenite recrystallization in AISI 1010 and AISI 1010 uith 0.02 pct Cb steels. For each steel the reduction in area given the specimen on the first pull was mainlairred at 30 ± 5 pct and recrystallization times deterntined at various temperatures. The results indicaled a significantly slower rate of recrystallization for the columbium-modified composition, suggested the presence of- a recovery stage in the softening process , and indicated a greatly increased softening rate at a temperatuve where significant allotropic transformation to a partially ferritic Structure could occur. In recent years increasing attention has been paid to the fact that the process of recrystallization of austenite deformed at elevated temperatures is far from instantaneous at many practical hot-working temperatures.1-3 This realization has given rise to such terms as hot cold-working1 or warm-working,2 These terms generally describe processes where the recrystallization rate at the temperature of deformation is slow enough to have an appreciable effect on mechanical properties despite a relatively high deformation ternperature. The mechanical properties of interest can be either the properties at the deformation temperature as in hot-workability studies4 or the room-temperature properties after cooling as in the many recent studies of various thermomechanical processes172 where heat treatment and deformation are intentionally combined to give a unique set of room-temperature properties. Because of this interest in processes where the austenite recrystallization kinetics can be an important variable, the development of quantitative methods of following the course of short-time, high-temperature recrystallization has received increasing attention.l,3,5 The experimental methods to date have, in general, relied upon rapidly deforming the austenite, holding at temperature for various brief intervals, quenching as G.A.WILBER and W. J. CHILDS, Members AIME,are Research-Fellow and Professor, respectively, Rensselaer Polytechnic Institute, Troy, N. Y. J. R. BELL and J. H. BUCHER, Member AIME, are Research Engineer and Research Supervisor, respectively, Graham Research Laboratory, Jones & Laughlin Steel Co., Pittsburgh, Pa. Manuscript submitted March 13, 1968. IMD. rapidly as possible, and then using room-temperature measurements to follow the recrystallization process. Although such methods can be successfully applied to certain alloy steels, the existence of the allotropic transformation during cooling of plain-carbon or low-alloy steels tends to obscure the results. Thus, such room-temperature measurements as hardness and X-ray line widths do not correlate well with the extent of austenite recrystallization before quenching,5 and results based on room-temperature microstruc-tural observations are dependent upon the success in correlating the observed structure with the prior aus-tenitic grain structure.1,3,5 The purpose of the present work was to develop a quantitative method for the determination of short-time, high-temperature recrystallization rates, based on measurements made at the temperature of deformation. EXPERIMENTAL TECHNIQUE The basic technique consisted of heating a small tensile specimen to a given temperature of hot deformation, loading to a given reduction in area, unloading, delaying various intervals at temperature, and then reloading to failure. The data were obtained in the form of traces of load and elongation as a function of time. Due to the high deformation temperature, the strain hardening introduced during initial loading was progressively annealed out with holding time after unloading and the loads obtained upon reloading decreased as this softening proceeded. Although the value of the second load at any Consistent point On the load-elongation curve could have been used as a measure of the degree of softening, the most convenient to use was the ultimate load. The softening indicated by the decrease in the second ultimate load with time is essentially a process of annealing of cold-worked material at a high deformation temperature. Although some recovery grain growth may contribute to such a softening process, it is generally considered that the major softening which must take place to achieve complete removal of substantial Strain hardening will occur by the formation of new, stress-free grains. As the results of this work indicate that essentially complete removal of strain hardening did in fact occur. the primary softening process will be attributed to recrystallization, and specific reference made where it appears that other mechanisms may be contributing to the total observed softening. It would, of course, be of interest to attempt to correlate the results of this work with the actual austenite fraction recrystallized as determined by other techniques. This was not attempted in the present work because it would have required running a large number of additional specimens and, as discussed previously, there is limited assurance that the results would accurately reflect the prior austenite fraction recrys-